Prevalence and predictors of sufficient physical activity using socio-ecological model among first-year undergraduate students of a University in Nigeria - Essiet, Inimfon Aniema (2016)
Introduction: The benefits of adopting regular and consistent physical activity as a lifestyle has been well documented. Research shows that regular participation in physical activity reduces the risk of chronic non-communicable diseases such as Type 2 diabetes mellitus, cardiovascular disease, some types of cancer and obesity. However, several studies have reported that physical activity begins to decrease in young adulthood when people transition from high school into the university. Studies have also reported that Nigerian university students do not engage in sufficient levels of physical activity required to gain the health benefits associated with being physically active. Physical activity is a health behavior that is determined by the interaction of various factors which may act as facilitators or barriers to being physically active. Thus, examining the multilevel determinants of physical activity using the socio-ecological model is an important prerequisite for designing relevant policies and effective health promotion programs aimed at increasing physical activity participation among Nigerian university students. Objective: This study was conducted to determine the prevalence and predictors of sufficient physical activity using the socio-ecological model among first-year undergraduate students of the University of Uyo, Nigeria. Methodology: A cross-sectional study was conducted in the University of Uyo in Akwa Ibom State, Nigeria. A total of 386 first-year undergraduate students were selected using a multistage sampling method. Data was collected on physical activity and associated factors among first-year undergraduate students from July to September 2015 using a self-administered questionnaire. The International Physical Activity Questionnaire (IPAQ) was used to assess physical activity levels of respondents. Respondents whose activity level was equal to or above 600MET-minutes/week were regarded as being sufficiently physically active. Descriptive analysis, chi-square tests and multiple logistic regression were conducted. Significant levels were set at p-value of <0.05 and 95% CI. Results: The response rate for this study was 88.6%. It was observed that 93.6% of the respondents were sufficiently physically active. Multiple logistic regression revealed that respondents belonging to the Ibibio ethnicity were more likely to be sufficiently physically active when compared to others (Adjusted OR = 3.510, 95% CI = 1.382, 8.916). Also, underweight and overweight respondents were less likely to be sufficiently physically active compared to those that were normal (Adjusted OR = 0.198, 95% CI = 0.064, 0.613 and Adjusted OR = 0.240, 95% CI = 0.077, 0.750 respectively). Furthermore, respondents who reported that there were school facilities for indoor recreation and that the school had an enjoyable scenery were more likely to be sufficiently physically active (Adjusted OR = 3.003, 95% CI = 1.179, 7.649 and Adjusted OR = 2.787, 95% CI = 1.074, 7.234 respectively). Conclusion: The findings of the study revealed that majority of the surveyed first-year undergraduate students of the University of Uyo demonstrated sufficient levels of physical activity over the course of seven days. Socio-ecological factors associated with physical activity that have been identified in this study can serve as additional information to aid in the development of interventions that would sustain high physical activity levels among university students.